PARTIAL PURIFICATION OF COLD ACTIVE LIPASE FROM PSEUDOMONAS SP. VITCLP4 ISOLATED FROM MARINE SAMPLES OF TAMILNADU COAST - M.KAVITHA; C.SHANTHI (International Journal of Pharma and Bio Sciences, 2014)
An extracellular cold active lipase from Pseudomonas sp. VITCLP4 was concentrated by two methods, ammonium sulphate precipitation and ultrafiltration. Ammonium sulphate precipitation with 40% saturation was found to give good results with 125-fold partially purified lipase and yield of 63%. Further purification by DEAE-Sephadex ion exchange chromatography resulted in 4.6-fold purified enzyme with yield of just 0.1%. This may be due to aggregation of protein during elution which is not reversible even after salt exchange. Therefore the enzyme could be partially purified with ammonium sulphate precipitation. Stability studies revealed that ammonium sulphate precipitate was 100% stable at -20oC for 10 days than other fractions. The molecular mass of cold active lipase was estimated to be approximately 52 kDa by SDS-PAGE.